Old-age Pension Provision in the EAEU Countries - V. V. Moseiko (Евразийская интеграция: экономика, право, политика, 2023)
The development of integration within the framework of the Eurasian Economic Union actualizes the issue of regulation of pension relations. The adoption of the Agreement on Pension Provision laid the foundations for international cooperation in the field of pension provision. However, significant institutional differences in national pension systems may hinder the effective implementation of oldage pension provision.Aim. To investigate the possibilities and difficulties of international cooperation in the pension sphere in the context of national differences in old-age pension provision in the countries of the Eurasian Economic Union.Tasks. To consider the national pension systems in terms of old-age pensions in the countries of the Eurasian Economic Union and conduct their comparative analysis; to show the features of international regulation of old-age pensions in the countries of the Eurasian Economic Union.Methods. In this work, the method of statistical data analysis was used to identify the features of the national old–age pension provision, comparative analysis — when comparing national pension systems in terms of old-age pensions, as well as the method of expert assessments when identifying difficulties of international cooperation in the pension sector.Results. Institutional features of old-age pension systems in the countries of the Eurasian Economic Union have been found. The grounds for international regulation of old-age pensions are revealed. Difficulties in the formation of pension rights of citizens of the Union countries have been found.Conclusions. The countries of the Eurasian Union faced similar economic and demographic challenges. Pension reforms have resulted in the design of pension systems with national institutional differences, which can become causes of social injustice and pension inequality.